2012
DOI: 10.1068/c1195r
|View full text |Cite
|
Sign up to set email alerts
|

Subsistence Farming, Incomes, and Agricultural Livelihoods in the New Member States of the European Union

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 24 publications
0
38
0
1
Order By: Relevance
“…This is known to be less harmful to biodiversity than conventional agriculture (Bengtsson et al 2005;Hole et al 2005), would be much more compatible with high nature value farmland (Kuemmerle et al 2009) and would not cause difficulties with respect to Natura 2000 regulations. In addition, Southern Transylvania most likely still exhibits unused potential to develop rural enterprises of greater value, such as agroenvironmental tourism or specialty foods (Davidova et al 2012). To realize this potential, local innovation capacity needs to be fostered.…”
Section: Rural Development Goals Cannot Be Pursued In Isolation From mentioning
confidence: 99%
See 1 more Smart Citation
“…This is known to be less harmful to biodiversity than conventional agriculture (Bengtsson et al 2005;Hole et al 2005), would be much more compatible with high nature value farmland (Kuemmerle et al 2009) and would not cause difficulties with respect to Natura 2000 regulations. In addition, Southern Transylvania most likely still exhibits unused potential to develop rural enterprises of greater value, such as agroenvironmental tourism or specialty foods (Davidova et al 2012). To realize this potential, local innovation capacity needs to be fostered.…”
Section: Rural Development Goals Cannot Be Pursued In Isolation From mentioning
confidence: 99%
“…Contrary to the EU-15 member states, the agricultural sector in Romania is largely dominated by subsistence and semisubsistence farming (Davidova et al 2012), resulting in part * Correspondence: Friederike Mikulcak e-mail: mikulcak@ leuphana.de from a profound land restitution process after the collapse of communism in 1989 (Stringer et al 2009;Vidican 2009). At the time of Romania's accession to the EU, more than 2.5 million people were employed in agriculture, with the average working farm area being only 3.2 ha (Gorton et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…(2009), Fritzsch et al. (2011), and Davidova et al. (2012) acknowledged this heterogeneity and employed cluster analysis to produce a typology of semi‐subsistence farmers.…”
Section: Introductionmentioning
confidence: 99%
“…A 2012 study in five new EU member states suggested that the largest cluster continues to be formed by the poorest households with "low natural, physical, and social capital, operating small-scale and undercapitalized farms with little nonagricultural income" (Davidova et al, 2012). The same study concluded that the specific needs of these poor subsistence farmers are not met by instruments of the EU Common Agricultural Policy (CAP) (Davidova et al, 2012). The CAP represents the EU's most important common policy, taking also a large percentage of the EU's budget (European Commission, 2017).…”
Section: Geographic Area Consideredmentioning
confidence: 99%
“…In the CEE region Poland, Romania and Hungary are the principal agricultural producers (Csaki and Jambor, 2009). In most cases, the return of land to private ownership in CEE countries has led to the creation of small semi-subsistence holdings (generally < 5 ha in size) and only a few very large industrial farms (Davidova et al, 2012;Sutcliffe 2015). environmental data analyses.…”
Section: Geographic Area Consideredmentioning
confidence: 99%